Incidental detection of elastofibroma dorsi on PET-CT: initial findings and changes in tumor size and standardized uptake value on serial scans. Issue 8 (August 2016) - Davidson, Tima; Goshen, Elinor; Eshed, Iris; Goldstein, Jeffrey; Chikman, Bar; Ben-Haim, Simona
Abstract : Objective: We describe changes in elastofibroma dorsi (EFD) as observed in serial fluorine-18 fluorodeoxyglucose ( 18 F-FDG) PET-computed tomography (CT) imaging studies. Materials and methods: 18 F-FDG PET-CT studies carried out between January 2006 and January 2015 at a single institution were reviewed by an experienced radiologist and nuclear medicine specialist. When available, previous or subsequent imaging studies were reviewed to evaluate changes in EFD. Results: Of 28 500 PET-CT studies carried out, EFD was identified in 68 from 20 patients (mean age 67.1±10.2 years; 14 women). Five patients had unilateral lesions and 15 patients had bilateral lesions. Eighteen patients had oncologic diseases. The mean size of EFD at first presentation was 13.95±5.90 mm and the mean homogeneous low-grade 18 F-FDG uptake was maximum standardized uptake value (SUVmax ) 2.24±0.95. One or more additional CT scans were performed in 17 patients; the mean interval between the first and last scans was 57.4±39.2 months. EFD was unchanged in size in 7/17 (41%) and showed slow growth in 10/17, reaching a mean size of 19 mm. The mean monthly growth rate was 0.1±0.10 mm. PET imaging in 11 patients showed a mean first SUVmax of 2.08±1.17 and a mean last SUVmax of 2.74±1.05 after a mean of 47.5±31.5 months ( P =0.63). Conclusion: Serial PET-CT studies may show a stable or slowly enlarging mass on a CT scan without changes in 18 F-FDG uptake on PET imaging. Familiarity with CT appearances and 18 F-FDG uptake of EFD are important for correct interpretation of 18 F-FDG PET-CT studies.